In situ UHVEM irradiation study of intrinsic point defect behavior in Si nanowire structures. Issue 3 (9th February 2015) - Vanhellemont, J.; Anada, S.; Nagase, T.; Yasuda, H.; Bender, H.; Rooyackers, R.; Vandooren, A.
Abstract Si nanowire‐based Tunnel‐Field Effect Transistor (TFET) characteristics are intensively studied as function of nanowire diameter and doping. A significant reduction of B diffusion with decreasing nanowire diameter is e.g. observed and attributed to reduced transient enhanced diffusion close to the nanowire surface caused by the recombination and out‐diffusion of excess self‐interstitials. In an Ultra High Voltage Electron Microscope (UHVEM), the formation of self‐interstitial clusters can be studied in situ while varying e‐beam flux, irradiation temperature, impurity concentration and capping layers surrounding the nanowires. Results are presented on 113‐defect formation in Si nanowires with diameters between 40 and 500 nm. The Si nanowires are embedded in SiO2 and are etched into an epitaxial Si stack on a heavily As doped Si substrate. The top layer of the epitaxial stack is in situ B doped or B implanted. In situ UHVEM studies are performed on focused ion beam prepared cross‐section samples, irradiating with different fluxes of 2 MeV electrons between room temperature and 375 °C. A strong dependence of 113‐defect formation on nanowire radius and doping is observed. The observations are compared with simulations based on quasi‐chemical reaction rate theory. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)